Analysis of Blunt Trauma-Related Optic Nerve Head Changes - Cem Özgönül; Osman Melih Ceylan; Tarkan Mumcuoğlu; Fazıl Cüneyt Erdurman; Volkan Hürmeriç; Gökçen Gökçe; Ali Hakan Durukan (Türk Oftalmoloji Dergisi, 2013)
Pur po se: To investigate the clinical and laboratory features of patients with traumatic optic disk pallor. Ma te ri al and Met hod: We retrospectively reviewed the records of 45 patients (47 eyes), who were diagnosed with traumatic optic disc pallor in our clinic between 2005-2010. Best-corrected visual acuity (BCVA), biomicroscopic and fundoscopic findings were recorded. Analysis of retinal nerve fiber layer (RNFL) and macular thickness maps, computerized visual field tests and visual evoked potentials (VEP) were evaluated. We compared the data of pathologic eyes with the data of healthy eyes. Re sults: The mean age was 22.3±3.8 (20-37) years. Twenty (44.4%) patients had traffic accident history, 9 (20%) - object trauma, 8 (17.8%) experienced work accident, and 8 (17.8%) had home accident history. BCVA was at the level of 20/40 (0.5) and above in seven eyes, between 20/200 (0.1) and 20/50 (0.4) in 20 eyes, counting fingers in 15 eyes, hand motion and light perception in three eyes, and no light perception in two eyes. There was thinning of RNFL in pathologic eyes at all quadrants (p<0.05). Dis cus si on: Traumatic optic disc pallor is associated with permanent loss of visual acuity and visual field. Relative afferent pupillary defect, prolonged VEP latency, and low amplitudes are useful for the evaluation of the cases. RNFL and macular thickness map analysis are important methods to evaluate the damage objectively. (Turk J Ophthalmol 2013; 43: 103-6)